Rectifier for RF energy harvesting using stub matching - I. Adam; M.N. M. Yasin; M.E. A. Aziz; Sulaiman M.I. (Institute of Advanced Engineering and Science, 2019)
One of challenge in rectenna design is the impedance matching of the antenna to the rectifier load. Rectifier exhibits complex impedance while antennas are normally designed to match either 50 Ω or 75 Ω loads. For the optimum power transfer between antenna and the rectifier circuit, both impedances should be matched. This paper presents the design and development of the 7-stages Dickson multiplier in energy harvesting. The objective of this paper is to analyze the performance of the designed multiplier together with matching circuit. An improvement of 60% output voltage is achieved by feeding -30dBm of low input power at the multiplier circuit.